Elemen Interior Jawa pada Ruang Rawat Inap Pasca Persalinan Berbasis Healing Environment - Isna Johanda, Almira Firdania; Santosa, Herry; Titisari, Ema Yunita (RUAS, 2024)
RSIA Melati Husada Malang developed the concept of a boutique hospital by applying Javanese architectural interiors to give a homey, personal, and authentic impression and support the healing environment concept. This aims to reduce anxiety and improve the well-being of postpartum patients. The purpose of this study is to identify the interior elements of Javanese architecture in the postpartum inpatient room that support the formation of a healing environment. The research uses a qualitative descriptive method with data sources from field observations. The criteria for identifying the object of study were developed by integrating literature studies on the interior elements of Javanese architecture and the concept of healing environment. This resulted in the formulation of 6 categories and 14 elements of Javanese architectural interiors, all of which adhere to the healing environment criteria. Furthermore, we use these criteria as a reference for descriptive analysis of the object of study. The results of this study show that the object of the study has applied 13 out of 14 criteria for Javanese interior design based on the healing environment.